LARANGAN LGBT MENJADI APARATUR SIPIL NEGARA DI KEJAKSAAN AGUNG - Zulfi, Danang Ardiansyah (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractTheppurpose ofpthis research ispto providepa solution to the letter Number: Peng-01 / C / Cp.2 / 11/2019 which contradicts the constitution (1945 Constitution) and Law 39/1999 concerning Human Rights. Usingpnormative researchpwith anporientation thatpis not conceptual.pThrough thispresearch, the researcherpoffers the regulations that must be made based on the 1945 constitution. At the time of the election of candidates for civil servants in 2019, there are opening positions for prison guards and prisoner drivers, the announcement is contained in Letter Number: Peng- 01/C/Cp.2/11/2019 in the specific requirements of paragraph (2) applicants may not have sexual orientation disorders and transgender decisions from the attorney general must be revoked because they violate the constitution and Law 39 of 1999 concerning Human Rights, the Attorney General's Office should make a selection based on ability (competence) candidates for civil servants are not based on sexual orientation and transgender disabilities.Keywords: human rights; LGBT; The 1945 Constitution, AbstrakTujuan penelitian ini adalah untuk memberi solusi dari SuratPNomor: Peng-p01/C/Cp.2/11/2019 yang bertentanganPdengan konstitusi (Undang-UndangpDasarp1945) danpUndang-Undang 39 Tahunp1999 tentangpHak AsasipManusia. Menggunakanppenelitian normatifpdengan orientasi yangptidak bersumber kepadapkonseptual. Melaluippenelitian ini peneliti menawarkan peraturan yang dibuat harus berdasarkan konstitusi Undang-Undang Dasar 1945. Pada saat pemilihan calon pegawai negeri sipil tahun 2019 membuka lowongan pengawal tahanan dan supir tahanan, pengumuman tertuang pada surat SuratpNomor: Peng-p01/C/Cp.2/11/2019 pada persyaratan khusus ayat (2) pelamar tidak boleh mempunyai kelainan orientasi seksual dan transgender keputusan dari kejaksaan agung ini harus di cabut karena melanggar konstitusi dan Undang-Undang 39 tahun 1999 tentang Hak Asasi Manusia seharusnya Kejaksaan Agung melakukan seleksi berdasarkan kemampuan (kompetensi) calon pegawai negeri sipil tidak berdasarkan Kelainan orientasi seksual dan Transgender.